MORTGAGE CREDITING SECURITIZATION MARKET - Vasilij M. Kartvelishvili; Anna V. Nikolaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article presents a model of the secondary market of mortgage crediting, whose basic aim is raising cheaper 'long' money to mortgage market. The authors describe key components of the model, identify their key characteristics, goals of functioning and analyze flows of interaction between model components. The article shows the origin of securitization and explains its role on the global finance market. The authors provide a review of key market indicators of Russian securitization market for some years. While analyzing the market principle trends of its development in Russia were shown and weak points of the market were highlighted. The article analyzes key problems hindering the active development of securitization model on Russian market, puts forward some ways of their resolving and provides recommendations aimed at attracting a bigger number of investors to mortgage reinvestment.